Optical Properties of Poly (vinyl alcohol) PVA Films Doped With Fe Citrate - Al-Taa'y, Wasan A (Al-Nahrain Journal of Science, 2018)
Pure and Fe citrate doped poly (vinyl Alcohol) PVA films with different concentrations (0, 0.5, 1.5, and 2) wt% were prepared by using casting technique. Optical absorption measurements in the wavelength range 200-800 nm were studied and confirmed that PVA films have an direct band gap that decreased from 5.47 to 4.79eV as the doping concentration increases to 2wt%. Optical constants such as absorption coefficient, refractive index, Extinction coefficient real and imaginary parts of dielectric constant have been studied; results show that the optical constants of the pure PVA films were increased after doping and with increasing impurity concentration. Urbach energy and optical conductivity were increases with the increasing of impurity concentration. The increase in the density of localized states Eu from 0.49 to 0.54eV causes an expanding in the Urbach tail and consequently decreases the energy gap.